1996
DOI: 10.1079/wps19960012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intermittent lighting, light intensity and source on the performance and welfare of broilers

Abstract: Broilers are currently reared under nearly continuous lighting (CL) schedules. However, the suitability of such lighting regimens may be questioned in terms of performance and welfare. This paper reviews the literature concerning the effects of intermittent lighting (IL) schedules on these issues. Final body weights at market age of broilers reared under IL schedules are equal to, or even higher than, those of broilers reared under CL schedules. However, endogenous (genotype and sex) and exogenous (dietary com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
59
1
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(70 citation statements)
references
References 45 publications
7
59
1
3
Order By: Relevance
“…Renden et al (1996) applied four different photoperiods: 1) 23L:1D; 2) 16L:8D; 3) 16L:3D1L:4D; 4) 16L:2D:1L:2D:1L:2D, where L = hours of light; and D = hours of darkness and did not find any influence of photoperiod on abdominal fat, wings, or thighs yields. However, Buyse et al (1996), when evaluating abdominal fat deposition in broilers submitted to intermittent (1L:3E) or nearly continuous (23L:1E) lighting programs found that the intermittent lighting program reduced broiler abdominal fat deposition at 28 and 41 days of age. These authors concluded that adipose tissue deposition was postponed due to a change in the slope of the growth curve imposed by intermittent lighting.…”
Section: Resultsmentioning
confidence: 99%
“…Renden et al (1996) applied four different photoperiods: 1) 23L:1D; 2) 16L:8D; 3) 16L:3D1L:4D; 4) 16L:2D:1L:2D:1L:2D, where L = hours of light; and D = hours of darkness and did not find any influence of photoperiod on abdominal fat, wings, or thighs yields. However, Buyse et al (1996), when evaluating abdominal fat deposition in broilers submitted to intermittent (1L:3E) or nearly continuous (23L:1E) lighting programs found that the intermittent lighting program reduced broiler abdominal fat deposition at 28 and 41 days of age. These authors concluded that adipose tissue deposition was postponed due to a change in the slope of the growth curve imposed by intermittent lighting.…”
Section: Resultsmentioning
confidence: 99%
“…These results are partially consistent with the findings of Classen (1992), quoted by Rutz et al (2000), that continuous lighting programs allow consistent access of the birds to the feed during the whole day, thereby promoting maximum feed intake and weight gain due to feed ingestion stimulation. Buyse et al (1996) evaluated the live performance of broilers submitted to intermittent (1 hour of light and 3 hours of dark) or nearly continuous (23 hours of light and 1 hour of darkness) lighting programs and showed that, up to 28 days of age, broiler body weight was higher with nearly continuous lighting program, but at 41 days, this difference disappeared and bird performance was similar at both programs. Renden et al (1996) observed an effect of the lighting program on weight gain, but not on the feed efficiency of 49-day-old broilers submitted to four different lighting programs.…”
Section: Resultsmentioning
confidence: 99%
“…A importância da luz nos aviários não está restrita apenas à duração da iluminação: intensidade da luz, fonte de luz, freqüência, comprimento de onda do pico de radiação, comprimento de onda espectral, composição espectral e a distribuição espacial das lâmpadas no galpão, também afetam os resultados finais, em termos da qualidade e da quantidade de produção (Buyse & Simons, 1996;Lewis & Morris, 1998).…”
Section: Introductionunclassified